1986
DOI: 10.1073/pnas.83.11.4094
|View full text |Cite
|
Sign up to set email alerts
|

Induction of nerve growth factor receptor in Schwann cells after axotomy.

Abstract: We have discovered that axotomy of sciatic nerve induces Schwann cells distal to the lesion to express de novo, or at greatly increased levels, receptors for nerve growth factor (NGF). Surgical transection of sciatic nerve was performed on adult Sprague-Dawley rats, and, at various times after the operation, the following tissues were dissected for quantitation of NGF receptor: L4 and L5 dorsal root ganglia, sciatic nerve proximal to the transection, sciatic nerve distal to the transection, tibialis anterior m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
277
2
5

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(298 citation statements)
references
References 35 publications
14
277
2
5
Order By: Relevance
“…It has recently been reported that the levels of NGF and its mRNA increase in the distal stump of rat peripheral nerve within a few days of nerve transection (Korsching et al, 1986), and that all Schwann cells in the stump markedly increase their expression of low-affinity NGF receptors during this period (Taniuchi et al, 1986). Taniuchi et al (1986) propose that NGF binds to cell-surface receptors of denervated Schwann cells and is subsequently transferred to the NGF receptors of regenerating axons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been reported that the levels of NGF and its mRNA increase in the distal stump of rat peripheral nerve within a few days of nerve transection (Korsching et al, 1986), and that all Schwann cells in the stump markedly increase their expression of low-affinity NGF receptors during this period (Taniuchi et al, 1986). Taniuchi et al (1986) propose that NGF binds to cell-surface receptors of denervated Schwann cells and is subsequently transferred to the NGF receptors of regenerating axons.…”
Section: Discussionmentioning
confidence: 99%
“…Taniuchi et al (1986) propose that NGF binds to cell-surface receptors of denervated Schwann cells and is subsequently transferred to the NGF receptors of regenerating axons. By this means, Schwann cells could provide both trophic support and tropic guidance to regenerating axons of NGFsensitive neurons, and, by expression of as-yet-unidentified agents, to axons of other neurons as well.…”
Section: Discussionmentioning
confidence: 99%
“…4). It is well documented in the literature that p75 is robustly induced in neurons, Schwann cells, and oligodendrocytes after injuries (Taniuchi et al, 1986;Koliatsos et al, 1991;Hayes et al, 1992;Roux et al, 1999). For instance, p75 has been reported to be induced in dying neurons after a seizure (Roux et al, 1999) and ischemia (Park et al, 2000) and in cortical neurons after experimental allergic encephalomyelitis (Calza et al, 1997;Nataf et al, 1998).…”
Section: P75 Activates Jnk1 and Jnk3mentioning
confidence: 98%
“…Functionally, macrophage activation within the DRG and peripheral nerve following peripheral nerve injury is known to help remove degenerating neuronal debris and myelin as well as contribute to subsequent regeneration (Lu and Richardson 1993, Perry and Brown 1992, Hu and McLachlan 2002. Recently, it has been recognized that inflammatory responses in the DRG may also contribute to the development pathological pain states (Cui et al, 2000;Xie et al, 2006) through the release of a variety of proinflammatory factors which are capable of sensitizing primary afferent neurons whose cell bodies are housed in the DRG (Taniuchi et al, 1986;Lindholm et al, 1987;Meyer et al, 1992;Hammarberg et al, 1996;Ma & Eisenach, 2002.…”
Section: Cellular Alterations In Satellite Cells Macrophages and Schmentioning
confidence: 99%